Discrete flavour symmetries, neutrino mixing and leptonic CP violation - S. T. Petcov (European Physical Journal C: Particles and Fields, 2018)
Abstract The current status of our knowledge of the 3-neutrino mixing parameters and of the CP violation in the lepton sector is summarised. The non-Abelian discrete symmetry approach to understanding the observed pattern of neutrino mixing and the related predictions for neutrino mixing angles and leptonic Dirac CP violation are reviewed. Possible tests of these predictions using the existing data on neutrino mixing angles as well as prospective data from current and future neutrino oscillation experiments (T2K, NO$$ν $$ ν A, Daya Bay, T2HK, T2HKK, DUNE) are also discussed.